Analyzing the Local Communities and Tourist Perception of Ecotourism in the Munsyari Area of Uttarakhand, India - Tolia, Ashna; Thiyaharajan, Muthuprasad; Arun Kumar, R.; Aiswarya, S. (Indian Forester, 2023)
Ecotourism, also known as bio-tourism or green tourism, is a responsible travel to pristine areas that helps in the upliftment of locals, heals nature, and maintains social and cultural integrity. Though ecotourism provides a wide array of benefits, it is often argued whether it is a panacea or a predicament. In this study, we tried to assess the perceptions of both locals and tourists regarding ecotourism. A total of 299 tourists and 100 households were surveyed using a structured and semi-structured interview schedule. Results revealed that ecotourism has a positive effect on the local people’s income as it provides various employment opportunities, which in turn reduces the out-migration of the locals. Though tourists were overall satisfied with the current scenario in Munsyari, they also raised concerns regarding poor garbage disposal and road facilities. The overall Willingness to Pay for Munsyari visit was around â‚¹672 per visit and the Willingness to Pay (WTP) has a positive association with awareness of ecotourism. A well-planned and managed ecotourism framework would help locals’ well-being, conservation of the environment and meet the needs of tourists.